Escherichia Coli Content in Refill Drinking Water (AMIU) in Samatiga District, West Aceh Regency - Azwar Azwar; Safrida Safrida; Yarmaliza Yarmaliza; Fitrah Reynaldi; Arfah Husna (Universitas Teuku Umar, 2020)
The quality of drinking water supply must be guaranteed. The WHO (World Health Organization) determines water quality by means of E. Coli bacteria. Based on the Minister of Health Regulation No. 492 / MENKES / PER / IV / 2010 The maximum permissible content of E. Coli in drinking water is 0 per 100 ml. The presence of E. coli in water is an indicator of human and animal fecal pollution that can cause diarrhea and even death. Selection of Refillable Drinking Water (AMIU) as an alternative to fulfill drinking water needs is a risk that can endanger health if the quality of AMIU is added if consumers do not pay attention to safety and hygiene. This study aims to see the content of E. coli in Refill Drinking Water (AMIU) in Samatiga District, West Aceh Regency. This research is experimental with cross sectional design using quantitative laboratory examination with the Most Probable Number (MPN) method. The population in this study were all refill drinking water depots that did not have a drinking certificate in Samatiga District, West Aceh Regency. The research sample used a total sampling method of 7 refill drinking water depots. The results of the analysis showed that from all samples as many as 6 samples (85.71%) tested positive for Escherichia coli bacteria and 1 sample (14.29%) tested negative for Escherichia coli bacteria. Based on the calculation of the number of colonies with the MPN / 100 ml table then comparing with the requirements of the Regulation of the Minister of Health of the Republic of Indonesia Number 492 / Menkes / Per / IV / 2010 concerning drinking water quality requirements that the 6 samples tested positive were not suitable for consumption.